VIDEO TRACKING BASED GRAVITY ACCELERATION ANALYSIS ON PENDULUM SWING - Angol, Yovita; Elot, Yolanita Murniaty (Journal of Learning and Technology in Physics, 2024)
This study aims to determine the acceleration of gravity on the pendulum swing with video tracking method. The research was conducted through video on a simple pendulum swing experiment. The recorded video is imported into the Tracker app to get the period and frequency for each trial with different rope lengths. The rope length and mass data were measured manually, and the period and frequency data were obtained through video tracking analysis. The research results are shown in tables and graphs. Data analysis used a linear regression equation between the square of the period and the length of the pendulum. The magnitude of the acceleration due to gravity is obtained through the gradient of the quadratic equation and the length of the rope. The results show that the acceleration of gravity through video tracking analysis is 9.735 m/s2 .Keywords: pendulum swing, video tracking, acceletiation of gravity